WOMEN AND LABOR MARKET: WORK FAMILY CONFLICT AND CAREER SELF-MANAGEMENT - França, Thais (Pensamento & Realidade, 2013)
The objective of the present study is to discuss and analyse the relation between the present labour market configuration and women’s professional career management. Because this is such an extensive topic, our discussion will focus mainly on Work Family Conflict (WFC) and Self-efficacy perception during a career transition period. Previous studies have focused, although not extensively, on such relationships. We intend to provide some additional clarification regarding these associations. The Participants were employees working at a Professional Center in Abruzzo, Italy. A multivariate analysis of variance (MANOVA) was conducted to evaluate the influence of Work-family conflict (WFC) on how women manage their career; the relations found among the variables in study were generally small. Mostly, WFC doesn’t influence on the career transition management process. Self-efficacy perception plays a role as a mediator between readiness level and Career Self Management. Results are discussed based on previous literature in the field of gender, work-family conflict and Career Management. Limitations of the study are discussed as well as directions for future researches are provided.